A review of the emission reduction potential of fuel switch towards biomass and electricity in European basic materials industry until 2030. (March 2020) - Rehfeldt, M.; Worrell, E.; Eichhammer, W.; Fleiter, T.
Abstract: In 2015, industrial sector installations included in the European emission trading system (EU ETS) emitted 574 Mt CO2 -equivalent Greenhouse gas (GHG) emissions. Among them are production of clinker, lime and ammonia, blast furnace operations, refineries and others. The emission intensity of these installations is closely tied to the fuel type used. Global warming scenarios of 1.5 °C recently presented by the IPCC require fast emission reduction in all sectors until 2030, followed by deep reductions, reaching carbon neutrality around 2050. In this paper, the technical potential to use biomass and electricity with existing or available technologies in important industrial processes is reviewed. The investigated industries account for 95% of the total verified emissions in the EU ETS industrial sector 2015 and 64% of total industrial emissions of the EU28. We find that 34% (184 Mt) of these emissions could be avoided from a technical perspective until 2030 with fuel switch measures towards biomass and electricity. This reduction is in line with 1.5 °C global warming scenarios until 2030, but further effort is required beyond that. We also find that available options lack economic competitiveness under present conditions, e.g. due to high electricity prices. We conclude that, although considerable fast emission saving potential by switching to biomass and electricity are possible, deep decarbonisation in line with climate targets requires innovative production processes only available in the long term. Graphical abstract: Image 1 Highlights: Fuel switch potential in cross-cutting and special processes is reviewed. Technical emission reduction potential of 34% until 2030 compared to 2010 is found. Potential in line with 1.5°C-scenarios. About 50% of emissions are not accessible by fuel switch.